Clinical Cases in Phototherapy - Koo, John.; Nakamura, Mio.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This case book will be based on real life scenarios of patient cases which have been encountered over several decades in one of the largest phototherapy centers in the United States. To our knowledge, there has not been anything similar published to date. By presenting various cases and how to manage such cases, we aim to educate dermatology trainees and practicing dermatologist who are trying to familiarize themselves with phototherapy. A recent study has shown that many dermatologists do not know how to administer phototherapy, and most graduating residents do not have adequate teaching and experience with administering phototherapy during their residencies. Therefore, the hope is that this book will fill a critical gap in the field of dermatology.
Ultraviolet B Phototherapy for the Treatment of Moderate to Severe Psoriasis -- PUVA for the Treatment of Moderate to Severe Psoriasis -- Excimer Laser for the Treatment of Mild to Moderate Psoriasis -- Goeckerman Therapy for the Treatment of Severe Generalized Psoriasis -- Avoiding Undertreatment with Phototherapy -- (3z(BErythemogenic(3y (BPhototherapy for Select Patients Who Need It -- Recognizing and Managing Initiation Burn -- Managing Phototherapy-Induced Burn -- When Patients Cannot Tolerate Narrowband-UVB -- Heliotherapy -- Cool Down before Initiation of Phototherapy -- Two-Step Phototherapy for Patients with Resistant Disease -- Phototherapy in the Setting of Photosensitizing Medications -- Phototherapy-Induced Iatrogenic Polymorphous Light Eruption -- Herpes Zoster During Phototherapy -- Enhancing Phototherapy with Topical Agents -- Combing Phototherapy with Acitretin: Re-PUVA and Re-UVB -- Combining Phototherapy with Methotrexate -- Combining Phototherapy with Cyclosporine (3z(BCool Down(3y (B-- Combining Phototherapy with Apremilast -- Combining Phototherapy with Biologic Agents -- Phototherapy for the Pediatric Population -- Phototherapy for the Elderly Population -- Phototherapy for Atopic Dermatitis -- Phototherapy for Vitiligo -- Phototherapy for Prurigo Nodularis -- Addressing the Question: Phototherapy and the Risk of Skin Cancer -- Prescribing a Home Phototherapy Booth -- Handheld Phototherapy Unit for Treatment of Localized Psoriasis or Scalp.s
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology